Climate Policy and the Optimal Extraction of High- and Low-Carbon Fossil Fuels - Edwin van der Werf; Sjak Smulders (Fondazione Eni Enrico Mattei (FEEM), 2007)
We study how restricting CO2 emissions affects resource prices and depletion over time. We use a Hotelling-style model with two non-renewable fossil fuels that differ in their carbon content (e.g. coal and natural gas) and in addition are imperfect substitutes in final good production. We show that an economy facing a CO2 flow-constraint may substitute towards the relatively dirty input. As the economy tries to maximise output per unit of emissions it is not only carbon content that matters: productivity matters as well. With an announced constraint the economy first substitutes towards the less productive input such that more of the productive input is available when constrained. Preliminary empirical results suggest that it is cost-effective to substitute away from dirty coal to cleaner oil or gas, but to substitute from natural gas towards the dirtier input oil.
Keywords: O13; Q31; Q43; 330; Climate Policy; Non-Renewable Resources; Input Substitution; Klimaschutz; Fossiler Energieträger; Luftverunreinigung; Kohlendioxid; Theorie